Contemporary evaluation and treatment of tricuspid regurgitation - Minciunescu, Andrei; Emaminia, Abbas (Frontiers in Cardiovascular Medicine, 2024)
Valvular heart disease is a global health burden with substantial mortality. The left-sided valvular diseases have been extensively described using the robust treatment strategies available. By contrast, the right-sided diseases, particularly the tricuspid valve (TV) and associated regurgitation, still have much to be delineated. Worsening tricuspid regurgitation (TR) is associated with increased mortality; the non-invasive management is suboptimal; and surgical approaches carry significant risk. With advances in multimodality imaging, 3D echocardiography, improved understanding of TV anatomy, and pathophysiological mechanisms of primary and secondary regurgitation, as well as favorable data with transcatheter therapies, the field of TV management is rapidly evolving. This review aims to highlight pathophysiological mechanisms of TR, describe echocardiographic approaches to diagnosis and TV interrogation, and outline the latest transcatheter developments.